Diseño de un prototipo de panel implementando la cáscara de cacao como materia prima - Lata Aguirre, Eliana del Rocío (2024)
This project focuses on designing a ceiling panel prototype using cocoa shells as raw material. By recycling this by-product and combining it with polyester resin as a binder, we aim to create a sustainable material that can be integrated into buildings. This initiative not only reduces waste but also lowers the carbon footprint associated with traditional construction materials. The objective is to characterize the raw material, develop prototypes according to national and international standards, experiment with different dosages, and analyze the panel's thermoacoustic properties. Ultimately, this innovative approach could revolutionize agricultural waste management and contribute to a more sustainable future in the construction industry. In this tesis. This project focuses on designing a prototype ceiling panel using cocoa shells as raw material. By recycling this by-product and combining it with polyester resin as a binder, the aim is to create a sustainable material for integration into buildings. This initiative not only reduces waste but also lowers the carbon footprint associated with traditional construction materials. The objectives are to characterize the raw material, develop prototypes according to national and international standards, experiment with different dosages, and analyze the panel's thermoacoustic properties. Ultimately, this innovative approach could revolutionize agricultural waste management and contribute to a more sustainable future in the construction industry. In this thesis, we will explore the design of a prototype panel that uses cocoa shells as raw material, thereby promoting more sustainable management of cocoa byproducts. To achieve this, the following actions will be undertaken: characterizing the raw material for prototyping, developing prototypes in accordance with national testing standards, experimenting with different dosages in the manufacturing of the models, characterizing the prototypes through physical and mechanical tests, and analyzing the panel's thermoacoustic properties through laboratory tests. The prototype of 50% cocoa shell and 50% polyester resin proved to be an effective option for ceilings, meeting density and stability standards. Its thermal performance is favorable for hot climates, and its mechanical strength is suitable for applications in lightweight construction systems.